Multimodal in vivo Imaging of the Integrated Postnatal Development of Brain and Skull and Its Co-modulation With Neurodevelopment in a Down Syndrome Mouse Model - Llambrich, Sergi; González, Rubèn; Albaigès, Julia; Wouters, Jens; Marain, Fopke; Himmelreich, Uwe; Sharpe, James; Dierssen, Mara; Gsell, Willy; Martínez-Abadías, Neus; Vande Velde, Greetje (Frontiers in Medicine, 2022)
The brain and skeletal systems are intimately integrated during development through common molecular pathways. This is evidenced by genetic disorders where brain and skull dysmorphologies are associated. However, the mechanisms underlying neural and skeletal interactions are poorly understood. Using the Ts65Dn mouse model of Down syndrome (DS) as a case example, we performed the first longitudinal assessment of brain, skull and neurobehavioral development to determine alterations in the coordinated morphogenesis of brain and skull. We optimized a multimodal protocol combining in vivo micro-computed tomography (µCT) and magnetic resonance imaging (µMRI) with morphometric analyses and neurodevelopmental tests to longitudinally monitor the different systems’ development trajectories during the first postnatal weeks. We also explored the impact of a perinatal treatment with green tea extracts enriched in epigallocatechin-3-gallate (GTE-EGCG), which can modulate cognition, brain and craniofacial development in DS. Our analyses quantified alterations associated with DS, with skull dysmorphologies appearing before brain anomalies, reduced integration and delayed acquisition of neurodevelopmental traits. Perinatal GTE-EGCG induced disparate effects and disrupted the magnitude of integration and covariation patterns between brain and skull. Our results exemplify how a longitudinal research approach evaluating the development of multiple systems can reveal the effect of morphological integration modulating the response of pathological phenotypes to treatment, furthering our understanding of complex genetic disorders.